Alternaria alternata, the Causal Agent of a New Needle Blight Disease on Pinus bungeana - Mao-jiao Zhang; Xiang-rong Zheng; Huan Li; Fengmao Chen (2023)
Pinus bungeana, an endangered and native coniferous tree species in China, has considerable timber and horticulture value. However, little is known about needle diseases in P. bungeana. A needle blight of P. bungeana has been observed in Hebei Province, China. P. bungeana inoculated with mycelial plugs of fungal isolates presented symptoms similar to those observed under field conditions. Ten virulent fungal isolates were identified as a small-spored Alternaria species based on morphological observations. Maximum likelihood and Bayesian phylogenetic analyses carried out with multilocus sequence typing of eight regions (SSU, LSU, ITS, gapdh, tef1, Alt a 1, endoPG, OPA10-2) assigned the pathogen to Alternaria alternata. This is the first report of A. alternata causing needle blight on P. bungeana in China.